Pengaruh Brand Image Dan Harga Terhadap Kepuasan Konsumen Pada Produk Kosmetik You PT Jalur Mandiri Utama - Nindy Tamara (JOURNAL ECONOMICS AND STRATEGY, 2023)
This study aims to determine tha effect of brand image on consumer satisfaction on YOU cosmetic products at PT Chanel mandiri utama, to determin the effect of price on consumer satisfaction on YOU cosmetic products from PT chanel mandiri utama, to determine the effect of brand image and price on consumer satisfaction on YOU cosmetic Products PT chanel Mandiri. Main. This research is a quantitative descriptive study with a questionnaire instrument, carried out on a number of populations, namely all consumers of PT. Medan’s Main mandir line which was obtained using accidental sampling, the size of the sample in this study was 50 people.